Grace Presupposes Nature: The Structure of the Summa and an Illustration by the Virtue of Patience in Light of Christ - Pellegrin, Tyler (European journal for the study of Thomas Aquinas, 2021)
The first part of this essay argues that the very structure and ordering of Thomas Aquinas’ Summa Theologiae manifests a departure from the typical theological position of his time regarding natural acquired virtues. Resting on a conviction that grace presupposes nature, Aquinas uniquely holds that natural virtues perfective of human nature can be acquired prior to grace, which can be elevated and incorporated by grace into the properly Christian life. The second part of this essay offers a case study of the virtue of patience that illustrates the argument of the first part of the paper.